Pierre Bayle and his reception in early eighteenth-century England: toleration in the Pensées Diverses and the Commentaire Philosophique - Hooks, J (2023)
This thesis offers an original interpretation of Pierre Bayle (1647-1706) and new insights into his reception in England after the Glorious Revolution (1688). Bayle was one of the most influential figures of the Enlightenment who formulated some of the first arguments for a universal toleration that extended even to atheists. Scholars usually speak of Bayle’s conception of toleration as if it were a singular theory. This thesis, however, contends that Bayle’s two most famous treatises on toleration, his Pensées diverses (1682) and his Commentaire philosophique (1686), introduced two notably different justifications for religious toleration. The Pensées used Calvinist resources to inspire a radically universal theory of toleration by arguing that due to original sin, individuals were self-interested and irrational, and since the church was a small remnant of predestined believers, an absolutist state (rather than religious uniformity) was needed to secure social harmony. In contrast, Bayle’s Commentaire argued that toleration was a universal matter of natural law, proven by innate axioms of reason. When Bayle wrote the Commentaire, he sought to appeal to a cross-confessional audience, avoiding doctrines such as predestination and original sin. He now depicted individuals as rational, the church as visible, and the state as limited by the rights of conscience. Bayle knew the Commentaire would not be read positively in his French Reformed community which stressed the weakness of human reason and volition, so he hid its authorship, unlike the Pensées which he had circulated amongst Calvinist ministers.